PELATIHAN PUBLIC SPEAKING UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI DAN KEPERCAYAAN DIRI - Buntoro, Ika Febianti; Folamauk, Conrad Liab Hendricson; Nurina, Rr Listyawati; Tanto, Ayu Cyntia; Handoyo, Nicholas Edwin (Universitas Nusa Cendana, 2023)
Public speaking is one of the skills needed in the global era and can affect success at work. With good communication, a person will be able to convey messages appropriately, build various relationships with many people and agencies, motivate others, and also be able to influence various decisions. Without good communication skills, misunderstandings will arise, reducing opportunities for building relationships and collaboration with other parties. However, public speaking often causes anxiety, stress, and intense negative behavioral responses. An initial survey by the team found that the faculty of medicine and veterinary medicine of Universitas Nusa Cendana (FKKH Undana) leadership had never received capacity-building training on public speaking. These inadequate speaking skills can undermine the ability to convey important messages or bore the audience. A person's lack of self-confidence will also hinder his/her self-development and make him pessimistic in facing challenges. Therefore, the community service team conducted public speaking training for leaders and the Undana FKKH academic community. In this activity, the participants were trained on the basics of public speaking, namely how to master themselves, master the material, and master the audience. This training received a positive response from the participants, where the participants felt an increase in their abilities and self-confidence. Public speaking can help speakers convey messages more precisely to the audience. The training is expected to improve performance in public speaking and overcome anxiety.